Принципы организации системы дистанционного обучения скорочтению на локально-параллельных нечетких алгоритмах - Михаль, О. Ф. (УАДО, 2002)
Principles are considereded of building of speed reading simulator using local-parallel fuzzy algorithms. Recommendations are given on its network realization and use within the remote education concept.
Keywords: дистанционное обучение; образование